Did you rule out neurosyphilis? - Nitrini,Ricardo (2010)
Abstract Neurosyphilis, formerly a frequent cause of dementia, is now a rare condition in developed countries. However, syphilis remains common in many developing countries, where adequate diagnosis and treatment of early syphilis may be lacking, increasing the chances of neurosyphilis and prevalence of syphilitic dementia. Objectives: To present cases of syphilitic dementia seen in a cognitive and behavioral neurology unit in Brazil, emphasizing their first symptoms and the challenges they posed in diagnosis. Methods: At our unit of the Hospital das Clínicas of the University of São Paulo, all patients are submitted to blood treponemal tests. When the test is positive, a lumbar puncture is performed. We retrospectivelly reviewed all cases of neurosyphilis seen in our unit from January 1991 to November 2009. Results: Nine cases of neurosyphilis (0.77% of the 1160 cases in our files) were identified over the period. Patients with neurosyphilis were all men, had a mean age of 47.8 (±13.0) years (median of 43 years), and presented with various neuropsychiatric syndromes and elusive diagnoses. The median time from onset of symptoms to diagnosis was 24 months and only one patient made a full recovery after treatment. Conclusions: Neurosyphilis is not frequent but remains present, causing several types of neuropsychiatric syndromes. As it is very simple to rule out neurosyphilis by performing a blood treponemal test, this test should be performed in all patients with neuropsychiatric symptoms, particularly in regions of the world where syphilis is still a commonly occurring disease.